Evolution of reproductive life‐history and dispersal traits during the range expansion of a biological control agent. (1st November 2022) - Clark, Eliza I.; Bitume, Ellyn V.; Bean, Dan W.; Stahlke, Amanda R.; Hohenlohe, Paul A.; Hufbauer, Ruth A.
Abstract: Evolutionary theory predicts that the process of range expansion will lead to differences in life‐history and dispersal traits between the core and edge of a population. At the edge, selection and genetic drift can have opposing effects on reproductive ability, while spatial sorting by dispersal ability can increase dispersal. However, the context that individuals experience, including population density and mating status, also impacts dispersal behavior. We seek to understand the shifts in traits of populations expanding across natural, heterogenous environments, and the evolutionary and behavioral factors that may drive those shifts. We evaluated theoretical predictions for evolution of reproductive life‐history and dispersal traits using the range expansion of a biological control agent, Diorhabda carinulata, or northern tamarisk beetle. We find that individuals from the edge had increased fecundity and female body mass, and reduced age at first reproduction, indicating that genetic load is low and suggesting that selection has acted at the edge. We also find that density of conspecifics during rearing and mating status influence dispersal of males and that dispersal increases at the edge of the range under certain conditions, particularly when males were unmated and reared at low density. The restricted conditions in which dispersal has increased suggest that spatial sorting has exerted weak effects relative to other potential processes. Our results support most theoretical predictions about evolution during range expansion, even across a heterogeneous environment, especially when the ecological context is considered.